Robust indirect field oriented control of induction generator - Bozhko, Serhiy; Peresada, Sergei; Kovbasa, Serhii; Zhelinskyi, M. (2017)
The paper presents a novel robust field oriented vector control for induction generators. The proposed controller exploits the concept of indirect field orientation and guarantees asymptotic DC-link voltage regulations when DC-load is constant or slowly varying. An output-feedback linearizing Lyapunov’s based technique is employed for the voltage controller design. Flux subsystem design provides robustness with respect to rotor resistance variations. Decomposition of the voltage and current-flux subsystems, based on the two-time scale separation, allows to use a simple controllers tuning procedure. Results of comparative experimental study with standard indirect field oriented control are presented. It is shown that in contrast to existing solutions designed controller provides system performances stabilization when speed and flux are varying. Experimentally shown that robust field oriented controller ensures robust flux regulation and robust stabilization of the torque current dynamics leading to improved energy efficiency of the electromechanical conversion process. Proposed controller is suitable for energy generation systems with variable speed operation.